Reconstruction of Lower Extremity Defects Using the Serratus Anterior Free Flap: A Systematic Review and Retrospective Case Series - Karir, Aneesh; Stein, Michael J.; Shiga, Sarah; Zhang, Jing (Journal of Reconstructive Microsurgery, 2020)
Background Free tissue transfer is the most common modality for distal third lower extremity reconstruction, yet complication rates remain high. The serratus anterior muscle free flap, which can be harvested alone or as a chimeric flap, is a robust and reliable option that remains the primary modality for distal third lower extremity defects at our institution. The objective of this study was to perform a systematic review of lower extremity reconstruction with the serratus anterior free flap and provide a retrospective review of cases at our institution.Methods A systematic review of the literature was conducted using PubMed, Embase, and Cochrane Library (PROSPERO CRD42018110692). Articles reporting reconstruction of lower extremity and foot defects using serratus anterior free flaps in adults were included. A retrospective cohort study of serratus anterior free flaps was then performed from 2012 to 2018 at our institution.Results Thirty-seven articles meeting inclusion criteria provided data on 198 flaps: 125 (63%) serratus-only flaps and 73 (37%) chimeric flaps based on the subscapular axis. Among the serratus-only flaps, defects were primarily due to chronic wounds (51%) or acute infections (33%). Flap survival rate was 97%, and the major and minor complication rates were 5 and 9%, respectively. Of the 10 cases included in the case series, flap survival rate was 100%, there were no major complications, and the minor complication rate was 44%. The average time to flap healing was 95 days and average lower extremity functional scale score was 58/80 among five patients.Conclusion Serratus anterior muscle free flaps are a versatile and reliable option for distal third lower extremity reconstruction.
Keywords: lower extremity reconstruction; serratus free flap; free tissue transfer